Study of nanostructured semiconductor metal oxide as visible-light photocatalyst - Tan, Pei Yun (2014)
Since the discovery of the “Fujishima-Honda” effect almost five decades ago, research on photocatalyst effect has been extensive and wide applications have been developed. These include water-splitting, removal of volatile-organic-compounds (VOCs), as well as disinfection for improved air and water quality. In recent years, there have been increasing global awareness to adopt more environmental-friendly approaches. Therefore, photocatalytic oxidation (PCO) process provides a clean alternative for disinfection and removal of environment pollutants and industrial wastes. The current market leader, titanium dioxide (TiO2) is limited by its large bandgap of 3.2 eV to be efficient only under UV light. In this research project, a low-cost and simple process which allows large-scale preparation of nitrogen-doped TiO2 was firstly explored and presented. By oxidizing nano-sized titanium nitride (TiN) powder, mixed phase TiO2 with visible-light absorption up to 525 nm was obtained. The powder oxidized at 500 °C demonstrated good Rhodamine B and gaseous toluene removal; in addition to E. Coli killing under the illumination of fluorescent light with λ > 435 nm. High-resolution X-ray photoelectron spectroscopy (XPS) was used to investigate the binding states of the nitrogen dopants and their effects on the overall photocatalytic performance. The charge separation efficiency was also studied through the powders’ surface photovoltage spectra and enhanced separation was observed at higher annealing temperature. Next, this project explored a new, potential candidate for visible-light active semiconductor photocatalyst with tailorable bandgap; in the form of strontium titanate ferrite (Sr(Ti1-xFex)O3-δ). Based on previous successful work by our research group on high energy ball-milled Sr(Ti1-xFex)O3-δ nanopowder, the project aim was to develop a fabrication process for Sr(Ti1-xFex)O3-δ thin films using sol-gel approach. Using a modified sol-gel based on Pechini’s method of polymerizable metal complex, Sr(Ti1-xFex)O3-δ thin films for the whole range of 0 ≤ x ≤ 1 had been successfully fabricated and characterized for its potential as visible-light photocatalyst. The devised fabrication protocol had produced uniformly coated thin films with good adhesion. The thin films had nanoporous surfaces which are beneficial for applications which require large surface-to-volume ratio. Optical study revealed bandgap reduction from 3.46 eV to 1.10 eV with increasing iron content. However, evaluation of their photocatalytic potential using Rhodamine B, bis-phenol A and stearic acid did not show obvious photocatalytic reaction despite their bandgaps which are in the visible-light range. Further investigation using XPS study showed the formation of oxygen vacancies needed to maintain charge balance. These defects can act as electron traps which prevented charge transfer to the film surface. Furthermore, the electronic conductivity of the films also increased with iron content. As a result, the films were unable to retain charge carriers long enough on their surfaces for meaningful redox reactions. These were supported by the surface photovoltage spectra where the magnitude of contact potential difference due to light illumination decreased with iron content and decayed quickly. More investigations and diverse characterizations need to be explored to overcome these issues. For example, co-doping of non-metals and noble metals could help to overcome the charge imbalance due to substitution of Ti4+ with Fe3+; thereby reducing the formation of oxygen vacancies. Another method could be restricting the amount of iron content to lower doping levels to limit the formation of oxygen vacancies while still extending the bandgap sufficiently into the visible-light range. Lastly, to increase surface area, other visible-light active photocatalyst can be embedded into the nanoporous structure of the films, which serves as holding matrix.